A novel approach to pulsed laser deposition of platinum catalyst on carbon particles for use in polymer electrolyte membrane fuel cells - Budner, Bogusław; Tokarz, Wojciech; Dyjak, Sławomir; Czerwiński, Andrzej; Bartosewicz, Bartosz; Jankiewicz, Bartłomiej (Beilstein Journal of Nanotechnology, 2023)
The research undertaken aimed to develop an efficient Pt-based catalyst for polymer electrolyte membrane fuel cells (PEMFCs) by using a cost-effective and efficient physical method to deposit platinum nanoparticles (PtNPs) on carbon supports directly from the platinum target. The method developed avoids the chemical functionalization of the carbon substrate and the chemical synthesis of PtNPs during catalyst fabrication. Platinum was deposited on carbon particles at room temperature using a pulsed laser deposition (PLD) system equipped with an ArF excimer laser (λ = 193 nm). The uniform deposition of PtNPs on carbon supports was achieved thanks to a specially designed electromechanical system that mixed the carbon support particles during platinum deposition. In the studies, Vulcan XC-72R carbon black powder, a popular material used as support in the anodes and cathodes of PEMFCs, and a porous carbon material with a high degree of graphitization were used as carbon supports. The best electrochemical measurement results were obtained for Pt deposited on Vulcan XC-72R. The peak power density measured for this material in a membrane electrode assembly (MEA) of a PEMFC (fed with H2/Air) was 0.41 W/cm2, which is a good result compared to 0.57 W/cm2 obtained for commercial 20% Pt Vulcan XC-72R. This result was achieved with three times less Pt catalyst on the carbon support compared to the commercial catalyst, which means that a higher catalyst utilization factor was achieved.
Keywords: carbon particles; cyclic voltammetry; fuel cells; ORR; PEMFCs; PLD deposition; Pt catalyst; rotating ring-disk electrode (RRDE); SEM; TEM; XPS